Endoscopic Resection of Early Gastric Cancer in Elderly - Da Hyun Jung (The Korean Journal of Gastroenterology, 2022)
With the aging of the society, the proportion of elderly patients with gastric cancer is increasing and the chances of encountering elderly patients with early gastric cancer (EGC) are increasing. Because elderly patients have more comorbidities, and lower life expectancy than younger patients, the treatment strategy for elderly patients with EGC is not standardized. Therefore, it is necessary to identify risk factors related to survival of elderly patients with EGC and to establish treatment strategies according to prognosis in elderly patients with EGC.